El tema de la morfología urbana en la historia del pensamiento geográfico - Bielza de Ory, Vicente (Geographicalia, 2014)
The Urban morphology, which in the early twentieth century began as a central theme of urban geography, when it was approached from a conception based on the landscape, linked to the natural framework and historical evolution, was stagnated with the New Geography, which had a spatial perspective, economistic, quantitative and more focused on structural issues. The recovery of the landscape in the eighties and the work of geographers in planning multidisciplinary teams have improved the situation of the morphology, especially in relation to the historic urban areas and post-industrial landscapes.